Leading Innovation - Shields, Kerri (Open textbook library., 2022)
Innovation today considers the economic, environmental, and/or social sustainability of an innovative initiative from its inception or idea generation through to its commercialization or implementation. This concept applies to many types of innovation such as products, processes, services, technologies, and business models. Companies use innovation as a means to gain a competitive advantage and bring value to business stakeholders. This book introduces business innovation, from incremental innovation such as enhancing the performance of an existing product, service, or process, to radical or disruptive innovation such as one that has a significant impact on a market. The content examines how leaders foster a culture of innovation, how companies turn creativity into innovation, and how innovation transforms not only organizations but economies as well.